Design of control algorithm based on high voltage transformer. Issue 1 (February 2021) - Shixi, Su; Hui, Luo; Zhikun, Liao
Abstract: Based on the application of transformers in switching power supplies, the article makes a kind of digital algorithm control. Through the 32 series' chip to control the start and maintain state of the equipment, the node voltage is continuously collected and the output is corrected in real time to ensure that the equipment remains stable. The article provides a complete algorithm design process and ideas including the calculation of the timer parameters, the configuration process of ADC voltage acquisition. Finally, the experimental verification is carried out to ensure the feasibility of the algorithm.